Pengaruh Literasi Perpajakan terhadap Kepatuhan Wajib Pajak: Studi Kasus Kantor Pelayanan Pajak (KPP) Pratama Bantul - Nistiana, Luthfia Dita; Wardani, Dewi Kusuma; Primastiwi, Anita (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study was conducted to test whether taxpayer compliance can be influenced by understanding tax regulations. This study was also conducted to determine whether there is a relationship between understanding of tax regulations and taxpayer compliance moderated by risk preferences. The method used in this study was conducted using the convenience sampling method using a sample of 100 respondents from individual taxpayers registered at the Tax Service Office (KPP) Pratama Bantul. The data used in this study is primary data through a questionnaire containing the respondents' answers. The data analysis technique is path analysis/path analysis with understanding of tax regulations being the independent/independent variable and taxpayer compliance being the dependent/dependent variable, and risk preferences being the moderating variable. The results of the analysis show that taxpayer compliance is influenced by the understanding of tax regulations. In addition, risk preferences also affect the relationship between understanding of tax regulations and taxpayer compliance. The implications of this study prove that understanding tax regulations is one element that has an important role in increasing individual taxpayer compliance at the Tax Service Office (KPP) Pratama Bantul.